Upper Molar Distalization with a New Tooth and Miniscrew Supported Appliance: A Clinical Study - Mehmet Bayram; Metin Nur (Galenos Yayinevi, 2010)
Aim:The aim of this study was to evaluate the effects of a new tooth- and bone-anchored intraoral appliance designed for upper molar distalization on dentofacial structures.Subjects and Methods:The study group comprised 11 patients (6 male and 5 female; mean age 13.5±1.8 years) with Class II molar relationship requiring molar distalization. A new appliance is designed to deliver a distalizing force to the upper molars for bodily distal movement. The appliance consists of a palatal sagittal screw and a miniscrew which was placed in the anterior paramedian region. The pretreatment and the post-distalization cephalometric radiographs were used to evaluate the distalization. The data were analyzed statistically by using a paired sample Student t-test at the 95%% confidence level.Results:The Class I molar relationships were achieved in a mean period of 5.1±0.6 months in all patients. The upper first molars showed a significant distalization of 3.9±1.5 mm (p<.001) and distal axial inclination of 3.5±2.4° (p=.001). As for anchorage loss, the upper first premolars (anchor teeth) and central incisor exhibited a significant mesial movement of 1.5±0.6 mm (p<.001) and 0.8±0.6 mm (p<.01), respectively.Conclusion:The results suggest that the new appliance is a minimal invasive, efficient and compliance-free device for bilateral maxillary molar distalization.